The complement system contributes to the pathology of experimental autoimmune encephalomyelitis by triggering demyelination and modifying the antigen-specific T and B cell response - Hundgeburth, Lorenz C.; Wunsch, Marie; Rovituso, Damiano; Recks, Mascha S.; Addicks, Klaus; Lehmann, Paul V.; Kuerten, Stefanie (Clinical Immunology, 2013)
So far, studies of the human autoimmune disease multiple sclerosis (MS) have largely been hampered by the absence of a pathogenic B cell component in its animal model, experimental autoimmune encephalomyelitis (EAE). To overcome this shortcoming, we have previously introduced the myelin basic protein (MBP)-proteolipid protein (PLP) MP4-induced EAE, which is B cell and autoantibody-dependent. Here we show that MP4-immunized wild-type C57BL/6 mice displayed a significantly lower disease incidence when their complement system was transiently depleted by a single injection of cobra venom factor (CVF) prior to immunization. Considering the underlying pathomechanism, our data suggest that the complement system is crucial for MP4-specific antibodies to trigger CNS pathology. Demyelinated lesions in the CNS were colocalized with complement depositions. In addition, B cell deficient JHT mice reconstituted with MP4-reactive serum showed significantly attenuated clinical and histological EAE after depletion of complement by CVF. The complement system was also critically involved in the generation of the MP4-specific T and B cell response: in MP4-immunized wild-type mice treated with CVF the MP4-specific cytokine and antibody response was significantly attenuated compared to untreated wild-type mice. Taken together, we propose two independent mechanisms by which the complement system can contribute to the pathology of autoimmune encephalomyelitis. Our data corroborate the role of complement in triggering antibody-dependent demyelination and antigen-specific T cell immunity and also provide first evidence that the complement system can modify the antigen-specific B cell response in EAE and possibly MS. © 2012 Elsevier Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: B cells; Complement; Demyelination; EAE/MS; MP4; T cells